An Analysis of Students’ Inhibition Level on Synchronous Class Using Video Conferencing - Karina Alya Rohmadi; Lilia Indriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2020)
The COVID-19 pandemic has successfully forced a global shutdown of several activities, including in educational sectors, and this has resulted a migration of universities with online learning as the educational media (Adedoyin & Soykan, 2020). However, the writer noticed that students are less responsive toward the lecturer’s words during the synchronous class using a videoconference. One of aspect that might create this situation is inhibition, which is sets of barricades to shield ones’ ego (Brown, 2000) or a temperamental proclivity to reveal caution, anxiety, or restraint in reaction to unfamiliar surroundings, objects, and circumstances (Kagan et all, 1988). Therefore the writer want to find out whether if the decreased intensity of students’ responsiveness is influenced by inhibition during the video conference classes. There were 33 students from Tidar University's English education department who participated in this study. The participants were received open-ended questionnaire adapted from Mohseni and Ameri (2010). The findings revealed that there are inhibition that students experienced during the learning process in IVC class. The most influencing factors are affective factors and the factors that come from classroom interaction, including the fear of language evaluation.